Hydrodynamic cavitation for lignocellulosic biomass pretreatment: a review of recent developments and future perspectives - Bimestre, Thiago Averaldo [UNESP] (2022)
The hydrodynamic cavitation comes out as a promising route to lignocellulosic biomass pretreatment releasing huge amounts of energy and inducing physical and chemical transformations, which favor lignin–carbohydrate matrix disruption. The hydrodynamic cavitation process combined with other pretreatment processes has shown an attractive alternative with high pretreatment efficiency, low energy consumption, and easy setup for large-scale applications compared to conventional pretreatment methods. This present review includes an overview of this promising technology and a detailed discussion on the process of parameters that affect the phenomena and future perspectives of development of this area.